Penggunaan Smart Mind Map dalam Pdp Pendidikan Moral (Sains Humanika, 2018)
This research identified the effectiveness of using Smart Mind Map in the teaching and learning of Moral education at Institut Kemahiran MARA (IKM) Bintulu. This quantitative study was conducted in two phases. The first phase employed a survey design and the survey data were obtained by using the questionnaire instrument while the second phase is employed a quasi-experimental design. A total of 47 students involved in this research. The validity of the data was determined by establishing reference from a panel of experts. The quantitative data were analysed descriptively and were inferred to obtain frequency, percentage, mean and standard deviation. As a result, it was found that the reliability of the instrument that was assessed via alpha Cronbach had been high, which was >80. The results show that the attitude of students is high and the use of Smart Mind Map provides a variety of benefits to students in the teaching and learning of Moral education. Quasi-experiments showed that the use of Smart Mind Map effective in improving students academic achievement. Thus, the use of Smart Mind Map need to be underway again and continuous efforts should be done to improve the function and effectiveness of Smart Mind Map in the teaching and learning of Moral education.
Keywords: Mind map; smart mind map; moral education; QR code